The intervention dilemma and high burden of children with autism in Guizhou province, Southwest China - Liu, Ye; Zhou, Fang; Qin, Jixuan; Lin, Yong; Li, Tonghuan; Zhu, Chengyong; Long, Fang; Wang, Xike; Hu, Xiao; Zhou, Hao (Frontiers in Psychiatry, 2022)
Background Autism spectrum disorder (ASD) is a highly disabling neurodevelopmental disorder, and the burden is high. Data on the burden of ASD are limited in China, especially in the southwest. Therefore, the aims of this study were to investigate the intervention status and burden of children with ASD in Southwest China. Materials and methods Families of children with ASD were recruited from hospitals, special education schools, and private rehabilitation centers; they participated in the survey and completed the questionnaire. Descriptive analysis was conducted on the questionnaire results, which included basic demographic characteristics, rehabilitation status, and burden. Multivariate analysis was used to analyze the association of basic family demographic characteristics, rehabilitation status, and costs of ASD. Results A total of 231 families of children with ASD participated in this survey, and 78.35% (181/231) of the children with ASD were male. The mean age was 4.34 ± 2.09 years. A total of 55.84% (129/231) of the children with ASD had an intellectual disability. Only 46.32% (107/231) started receiving intervention within 1 month after diagnosis. The institutions for rehabilitation interventions for children with ASD were mainly tertiary hospitals (39.39%), special education schools (29.87%) and private rehabilitation institutions (21.64%). For a total of 42.86% (99/231) of the children with ASD, the duration of the intervention was less than 10 h per week. A total of 74.89% (173/231) of the children with ASD received a rehabilitation intervention at home. A total of 66.67% of the parents were satisfied with the treatment. The monthly cost of medical intervention for the patients of children with autism was 7,225 ± 474 RMB ($1,134 ± 74), and the non-medical intervention cost was 2,133 ± 107 RMB ($334 ± 17). The annual burden of patients with autism was 86,700 ± 5,688 RMB ($13,596 ± 892). The estimated total annual burden of ASD was 5.548 billion RMB ($870 million) in Guizhou province. Conclusion The results revealed that rehabilitation resources are limited and that the burden of ASD is high in Guizhou province; therefore, improving the rehabilitation status and easing the burden of children with ASD is urgent in these regions.